Rs2015 Polymorphism in miRNA Target Site of Sirtuin2 Gene Is Associated with the Risk of Parkinson's Disease in Chinese Han Population. (12th May 2019) - Chen, Xiongjin; Mai, Hui; Chen, Xiaoting; Cai, Yujie; Cheng, Qiufei; Chen, Xiaoyi; Li, Xiaohui; Fan, Weihao; Tang, Pei; Ou, Mingqian; Yang, Jingqi; Chen, Yusen; et al.
Abstract : Accumulating evidence reveals that the sirtuin family is involved in the pathology of Parkinson's disease (PD). However, the association between the polymorphisms of the sirtuin gene and the risk of PD remains elusive. Here, we investigated the possible association of nine SIRT1 and SIRT2 SNPs with the risk of PD through a clinical case-control study from the Chinese Han population. Our results showed that rs12778366 in the promoter region of SIRT1 and rs2015 in the 3′untranslated region (3′UTR) of the SIRT2 were significantly associated with the risk of PD. Five SNPs related to SIRT1, rs3740051, rs7895833, rs7069102, rs2273773, and rs4746720 and two SNPs related to SIRT2, rs10410544, and rs45592833 did not show an association with PD risk in this study. Moreover, we found that mRNA level of SIRT2 was upregulated, and mRNA level of SIRT1 was downregulated in the peripheral blood of PD patients compared with healthy controls, and we also observed that SNPs rs12778366 and rs2015 influenced the SIRT1 and SIRT2 expression levels, respectively. Further functional assays suggest that rs2015 may affect the expression of SIRT2 by affecting the binding of miR-8061 to the 3′UTR of SIRT2, ultimately contributing to the risk of PD.